2022
DOI: 10.21203/rs.3.rs-1584298/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of Synthesis of Biogenic Hematite Nanocubes for environmental Assessment and its innovative Applications associated with Antibacterial, Antifungal, and Antioxidant activity

Abstract: Nanotechnology is a remarkable platform for water treatment and mitigation from microorganisms and organic dyes when compared to traditional treatment methods. This research work provides the solution to water pollution by magnetic nanoparticles (NPs) through a Fenton-like reaction at neutral pH and also the reusability of wastewater for wheat seeds growth. Benchmarking of obtained results revealed that the synthesized Fe2O3 nanoparticles (IONPs) degrade methylene blue (MB) dye only in 10 min (k1= 0.3387 min-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our research encompasses an in-depth investigation of the antibacterial potential, antioxidant efficacy, and mineralization capabilities of these NPs. The findings of this study show the novel synthesis of hematite, and eggshells play an important role in the generation of well-defined, non-agglomerated, spherical NPs with enhanced antioxidant properties as compared to the previous literature [19]. Eggshell-mediated hematite NPs demonstrate the formation of hydroxyapatite.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our research encompasses an in-depth investigation of the antibacterial potential, antioxidant efficacy, and mineralization capabilities of these NPs. The findings of this study show the novel synthesis of hematite, and eggshells play an important role in the generation of well-defined, non-agglomerated, spherical NPs with enhanced antioxidant properties as compared to the previous literature [19]. Eggshell-mediated hematite NPs demonstrate the formation of hydroxyapatite.…”
Section: Introductionmentioning
confidence: 57%
“…The maximum antioxidant activity achieved by Das el al. [19] was 72.73%, with 800 g/mL concentration of NPs. FTIR spectra showed that the presence of polyphenols groups worked as beneficial antioxidants [49,50].…”
Section: Antioxidant Studymentioning
confidence: 96%